Efficiency analysis of control actions and fighting fires in the Brazilian Legal Amazon: the case of the State of Tocantins - Rezende, Cláudia da Silva Aguiar; Rodrigues, Waldecy; Silva, Wilians dos Santos; Sousa, Paulo Augusto Barros de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
The present study aims at analyzing the efficiency of control actions and firefighting in the municipalities of the State of Tocan-tins. For this, the Data Envelopment Analysis (DEA) model was applied, constant returns, orientation to input and output. Among the municipalities analyzed (101), only 5 showed 100% efficiency (Benchmarking), that is, that they used the inputs in an optimi-zed way. The model showed a pattern of per capita expenditure per performance. Thus, inefficient municipalities should improve the quality of expenditures per capita per unit of performance, contributing to reduce the number of outbreaks of fires.